Perlindungan Hukum Masyarakat Adat terhadap Hak Ulayat dalam Pengelolaan Sumber Daya Alam: Studi tentang Perlindungan Hukum Masyarakat Adat terhadap Hak Ulayat dalam Pengelolaan Sumber Daya Alam di Kabupaten Luwu Timur - Hamra, Hamra; Nur, Abdul Rahman; Salmi, Salmi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is motivated by the gap between the constitutional recognition of indigenous peoples and the reality of customary rights protection, which are often neglected by investment interests and the state's right to control. Although Article 18B Paragraph 2 of the 1945 Constitution guarantees the existence of indigenous peoples, this recognition is conditional and weak in technical implementation. The main problem in this study is the ineffectiveness of East Luwu Regency Regional Regulation Number 1 of 2022 in protecting the customary rights of the Padoe Indigenous Peoples from mining company expansion. The research method used is normative juridical with a statutory and conceptual approach. The results show that the recognition of customary rights in the Basic Agrarian Law is still sectoral and has not been followed by comprehensive special legislation. In East Luwu Regency, the role of the local government is still very limited due to the lack of an inventory of customary territories and the existence of sectoral egos in natural resource management. In conclusion, de jure recognition does not automatically provide de facto protection for indigenous peoples without the government's political will to implement the regulation effectively. Researchers recommend accelerating the formation of the Customary Law Communities Law and establishing specific customary land boundaries through a Regent's Decree to ensure legal certainty and justice for indigenous communities.